The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4103/0301-4738.146747
|View full text |Cite
|
Sign up to set email alerts
|

High-risk histomorphological features in retinoblastoma and their association with p53 expression: An Indian experience

Abstract: Introduction:Histopathological features in retinoblastoma are considered high-risk factors (HRF) for tumor progression and metastasis, thus their presence becomes an indication for adjuvant chemotherapy. Present study was undertaken to evaluate the incidence of HRF in retinoblastoma and to correlate them with p53 expression.Materials and Methods:This was a retrospective study where 17 diagnosed cases of retinoblastoma were included. Cases were re-evaluated for various histomorphological parameters. Immuno-hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
(24 reference statements)
0
12
0
Order By: Relevance
“…In the series of Darwich and associates [32], it was reported that patients with choroidal invasion were more likely to develop systemic metastasis compared to the ones with or without optic nerve invasion ( P =0.0001). Choroidal invasion has also been found to correlate with molecular prognostic markers such as TP53 unlike other high risk factors (HRF) as it was once reported by Seema and associates [33] in India.…”
Section: Discussionmentioning
confidence: 85%
“…In the series of Darwich and associates [32], it was reported that patients with choroidal invasion were more likely to develop systemic metastasis compared to the ones with or without optic nerve invasion ( P =0.0001). Choroidal invasion has also been found to correlate with molecular prognostic markers such as TP53 unlike other high risk factors (HRF) as it was once reported by Seema and associates [33] in India.…”
Section: Discussionmentioning
confidence: 85%
“…This is slightly higher than some case series that quote an incidence of high-risk features in RB to be 40%-50%. [10] In 15% of the children, more than one risk feature were observed. These high-risk features are a concern mainly because they are associated with high incidence of extraocular relapse and low chances of recovering vision.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy if administered alone has inadequate central nervous system penetration and therefore can result in extraocular relapse. [10] We would like to emphasize that children with a white reflex must be screened at the earliest for underlying RB. Considering that it is the most common symptom and is likely to be picked up even in a photograph, it is important to sensitize the general pediatricians to routinely screen the children during vaccination visits.…”
Section: Discussionmentioning
confidence: 99%
“…Various IHC studies in RB pathology have shown prognostic clues for understanding the biology of this childhood cancer. [ 1 2 3 4 5 6 7 8 ] We took up the study to know the characteristics of newly described rosettes with various known immunomarkers for RB. The new rosettes were associated with histopathological high-risk factors and morphologically different from FW and HW rosettes.…”
Section: Discussionmentioning
confidence: 99%